(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Juvenile rheumatoid arthritis (JRA) is a chronic autoimmune disease of childhood, accompanied by joint inflammation and systemic complications. The study included a correlation analysis of eight immunological parameters in children with JRA. Reliable relationships were found between IL-8, IL-17A and INFγ, based on which the disease prognosis index (DPCI) was calculated. The highest DPCI values were observed in the seropositive form of JRA, which correlated with the severity of the clinical picture. The IL-17A/INFγ ratio can serve as an important prognostic marker. The data obtained are of diagnostic and practical importance for treatment optimization.